MAMMOPLASTY: FROM RECONSTRUCTIVE TO AESTHETIC SURGERY - A.A. TERKULOV; E.E. DEVLIKANOVA; V.E. KOLESNIKOV (Avicenna Tajik State Medical University, 2022)
Mammoplasty is one of the most common operations, both among aesthetic and reconstructive interventions on the mammary gland. Over the past 10 years, the number of women newly diagnosed with malignant tumors of the mammary gland in Russian Federation is annually increasing, on average, by 3.6% (more than 46 thousand new cases): in 2019, 73,918 new cases of breast cancer (BC) were detected. Currently, the treatment of BC involves the removal of the primary tumor, followed by reconstruction of the gland, which plays an important role in the early rehabilitation of patients. In plastic surgery, breast augmentation interventions occupy one of the leading positions with an annual upward trend. The review article presents the history of the development of oncoplastic surgery, justifies the need for primary reconstructive surgery in women with BC, and describes options for radical mastectomies with one-stage reconstruction. Literature data on indications for breast implants, the main methods of augmentation mammoplasty and lifting, and transplantation of autologous adipose tissue enriched with stem cells in severe ptosis are presented; post-lactational or age-related involution of the mammary glands is described.